2021
DOI: 10.3389/fmicb.2021.735767
|View full text |Cite
|
Sign up to set email alerts
|

Effects of N Fertilization During Cultivation and Lactobacillus plantarum Inoculation at Ensiling on Chemical Composition and Bacterial Community of Mulberry Silage

Abstract: As unconventional forage source, mulberry (Morus alba L.) has been cultivated to alleviate animal feed shortages. This study aimed to investigate the effects of N fertilization during cultivation and Lactobacillus plantarum inoculation at ensiling on the chemical composition and bacterial community of mulberry silage. Mulberry was separately cultivated under two N fertilization rates (N1, 390 kg/ha/year; N2, 485 kg/ha/year) in 2016–2019, harvested on 30 April (the first-cut) and 15 June (the second-cut) in 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
2
1
0
Order By: Relevance
“…At the same time, we observed that the WSC concentration of the CK group decreased to 18.52 g.kg −1 DM on the 7th day, which may be due to the increasing consumption of WSC caused by the propagation of undesirable microorganisms in the early stage of ensiling (Li et al, 2022). Similar to our findings, a previous study (Li et al, 2021) demonstrated that inoculation with additives could retain more WSC in mulberry silage. We also discovered that the WSC concentration increased with increasing EDTA concentration, possibly because the high concentration of EDTA inhibited the activity of harmful microorganisms, decreased the utilization of WSC.…”
Section: Chemical Composition Of Paper Mulberry Silagesupporting
confidence: 93%
“…At the same time, we observed that the WSC concentration of the CK group decreased to 18.52 g.kg −1 DM on the 7th day, which may be due to the increasing consumption of WSC caused by the propagation of undesirable microorganisms in the early stage of ensiling (Li et al, 2022). Similar to our findings, a previous study (Li et al, 2021) demonstrated that inoculation with additives could retain more WSC in mulberry silage. We also discovered that the WSC concentration increased with increasing EDTA concentration, possibly because the high concentration of EDTA inhibited the activity of harmful microorganisms, decreased the utilization of WSC.…”
Section: Chemical Composition Of Paper Mulberry Silagesupporting
confidence: 93%
“…Compared with the CK, the additive treatment significantly (P < 0.05) increased the WSC content. Similar results were obtained by Li et al (2021a), who reported that inoculation with additives increased the WSC content of mulberry silage. AVEO treatment significantly (P < 0.05) decreased the NH 3 -N content compared with that in the CK silage.…”
Section: Chemical Compositions Of Fresh and Ensiled Paper Mulberrysupporting
confidence: 89%
“…However, consistent results were reported by Sun et al (2022), who found that silage additives can increase the NDF and ADF levels in PM silage. This result might be attributed to the reduction in DM content (Li et al, 2021a). The WSC content in forage plays an essential role in the production of LA during ensiling.…”
Section: Chemical Compositions Of Fresh and Ensiled Paper Mulberrymentioning
confidence: 99%